Tinggi Badan dan Berat Badan sebagai Prediktor Performa Kelincahan pada Pemain Voli Putri Profesional - Khoirun Nisak; Taufik Rahman; Rendra Kusuma (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This research explores the relationships among height, weight, and agility in professional female volleyball players. The study employed a quantitative, correlational, and cross-sectional design. The participants were 14 professional female volleyball athletes who met the inclusion criteria. Height was measured using a SECA 213 stadiometer, weight with a TANITA BC-545N, and agility was measured using the T-Agility Test. Descriptive statistics and Pearson correlation analyses were performed using IBM SPSS Statistics 20.0 (α=0.05) to examine the research data. The average height of participants was 171.86±4.97 cm, weight 65.17±5.57 kg, and agility time 11.05±0.44 seconds. The results of the Pearson correlation test showed that height had a strong positive relationship with agility (r=0.782, p<0.01), while weight showed a moderate positive relationship with agility (r=0.577, p<0.05). There was a significant positive relationship between height and agility, and weight and agility among professional female volleyball athletes. Participants with greater height and weight tended to take longer to complete the agility test.